2010
DOI: 10.4236/jwarp.2010.28088
|View full text |Cite
|
Sign up to set email alerts
|

16-23S rRNA Spacer Region Polymorphism in Gangetic River Water Isolates of Salmonella

Abstract: Salmonella is one of the major pathogenic bacteria present in contaminated water. 16-23S rRNA spacer region has been reported to be polymorphic at serovar level in Salmonella. Salmonella isolates obtained from Ganges river water were studied for 16-23S rRNA spacer region polymorphism. Thirty three isolates belonging to eight serovars (S. Typhimurium, S. Abuja, S. Pantypridd, S. Lagos, S. Chinkual, S. Zwickau, S. Goldenberg and S. Oritamerin) were studied for the polymorphism. Out of 33 isolates, 15 different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…13 The Ganges River is considered as the lifeline of the Indian subcontinent and its microbial load is continuously increasing. Singh and Saxena (2010) 14 isolated thirty three isolates of Salmonella belonging to eight serovars from the Ganges water, India. Studies also showed that the addition of untreated sewage waste in river bodies has increased the prevalence of fecal origin Salmonella in different stretches of Ganges River, which is used majorly for drinking and domestic work.…”
Section: Introductionmentioning
confidence: 99%
“…13 The Ganges River is considered as the lifeline of the Indian subcontinent and its microbial load is continuously increasing. Singh and Saxena (2010) 14 isolated thirty three isolates of Salmonella belonging to eight serovars from the Ganges water, India. Studies also showed that the addition of untreated sewage waste in river bodies has increased the prevalence of fecal origin Salmonella in different stretches of Ganges River, which is used majorly for drinking and domestic work.…”
Section: Introductionmentioning
confidence: 99%